Efficient, wide angle, structure tuned 1 x 3 photonic crystal power splitter at 1550 nm for triple play applications - Tee, D.C.; Kambayashi, T.; Sandoghchi, S.R.; Tamchek, N.; Adikan, Faisal Rafiq Mahamd (Institute of Electrical and Electronics Engineers, 2012)
We propose a wide angle, efficient and low loss 1 x 3 power splitter based on triangular lattice air holes silicon slab Photonic Crystal (PhC). Desired power splitting ratio was achieved by altering the structure at the junction area of the power splitter. Simulation results obtained using 2-D finite difference time domain method show that for TE polarization incident signal, the power is distributed almost equally with total normalized transmission of 99.74 and negligible reflection loss at the 1550 nm optical operating wavelength. In addition, the power splitter can operate at 1388 nm and 1470 nm optical wavelengths.